Deformation Response and Safety Evaluation of Buildings Affected by Subway-Station Construction - Chunlei Feng; Dingli Zhang; Hualao Wang; Xuan Zhang (Advances in Civil Engineering)
Based on the sand and pebble stratum in the Beijing area, this paper studies the interaction between deep-foundation-pit excavation for subway stations and surrounding buildings using an orthogonal test. Moreover, it considers the relative position relationship between buildings and how the foundation pit is set up as well as different design schemes for foundation pits and the surrounding buildings. Results show that the horizontal distance s between the building and foundation pit and stiffness of the building itself have a clear impact on the differential settlement δij and relative deflection Δ, and the degree of deformation of the building near the corner of the foundation pit is complex. Simultaneously, based on numerical simulation results, the deformation characteristics and degree of deformation of the building under different relative position relationships with the foundation pit are analyzed. Finally, by establishing a relationship among the comprehensive deformation index Dj, surrounding environmental safety evaluation index Sj, and scheme safety grade Lj, a multiangle safety evaluation method for buildings affected by foundation-pit construction is formed, which can provide a reference for the research and design of similar projects.